2009
DOI: 10.1177/0269216309106460
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life care in hospital: a descriptive study of all inpatient deaths in 1 year

Abstract: The objectives of this study are to ascertain how many patients who died in a district general hospital in England might have been able to be cared for at home, to obtain the cost of each inpatient stay, to make an estimate of the maximum resource implications of care packages for these patients, and to calculate the savings in hospital admissions that could be used for the development of community services. These objectives are dependant on full implementation of the End of Life Strategy. A descriptive study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 6 publications
0
67
4
Order By: Relevance
“…A third study 82 was a descriptive analysis of the change in usage and costs of health-care services following the introduction of two community-based services in Boston, Lincolnshire, as part of the Marie Curie Delivering Choice Programme to develop services that allow people to be looked after and die in the place of their choice. The final two studies 79,83 were retrospective analyses of patient records for patients who had died in hospital to estimate the proportion of final admissions that could be classified as avoidable.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A third study 82 was a descriptive analysis of the change in usage and costs of health-care services following the introduction of two community-based services in Boston, Lincolnshire, as part of the Marie Curie Delivering Choice Programme to develop services that allow people to be looked after and die in the place of their choice. The final two studies 79,83 were retrospective analyses of patient records for patients who had died in hospital to estimate the proportion of final admissions that could be classified as avoidable.…”
Section: Resultsmentioning
confidence: 99%
“…The two retrospective studies reported a high level of potentially avoidable admissions. Abel and colleagues 79 concluded that up to one-third of final admissions were avoidable; at least 20% were defined as 'clearly avoidable' and 13% as 'probably avoidable'. These assessments were based on the assumption that the End of Life Care Strategy for England 5 was fully implemented and services always had capacity.…”
Section: Evidence Regarding the Scale Of Avoidable Admissionsmentioning
confidence: 99%
See 3 more Smart Citations